2018
DOI: 10.1002/hed.25472
|View full text |Cite
|
Sign up to set email alerts
|

Short telomere length in peripheral blood leukocytes in head and neck cancer: Findings in a Brazilian cohort

Abstract: Background Telomeres are specialized DNA structures that are critical to maintain cell homeostasis and to avoid genomic instability. Epidemiological studies have examined the association between leukocyte telomere length (LTL) and risk of cancers, but the findings remain conflicting. Methods Mean LTL was measured by quantitative PCR in 97 patients with head and neck cancer (HNC) and 262 healthy controls. The association between LTL and patients' clinical status, such as smoke, alcoholism, and overall survival,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…On the other hand, other studies have revealed shortened telomeres in peripheral blood leukocytes obtained from patients with HNSCC compared to healthy controls. As found by Alves-Paiva et al in a Brazilian cohort of HNSCC patients, the median relative LTL was lower in HNSCC patients compared to age-matched healthy individuals, and this was associated with increased risk of HNSCC (14). Similarly, Barczak et al have reported the presence of shorter telomeres even in early stage HNSCC tumors (40).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…On the other hand, other studies have revealed shortened telomeres in peripheral blood leukocytes obtained from patients with HNSCC compared to healthy controls. As found by Alves-Paiva et al in a Brazilian cohort of HNSCC patients, the median relative LTL was lower in HNSCC patients compared to age-matched healthy individuals, and this was associated with increased risk of HNSCC (14). Similarly, Barczak et al have reported the presence of shorter telomeres even in early stage HNSCC tumors (40).…”
Section: Discussionsupporting
confidence: 51%
“…Several studies have shown an association between changes in peripheral venous blood leucocyte telomere length (LTL) and cancer development (13). Raquel et al have found the association between short telomeres and head and neck cancer development (14). However, the literature data on this matter are rather controversial.…”
mentioning
confidence: 99%
“…Despite the obvious credentials that telomeres have as potential drivers of oncogenic transformation and cancer progression, the literature is full of studies that associate (normal) peripheral blood leukocyte telomere length to cancer pathologies [29][30][31][32][33][34]. As 4 cancer can be viewed as an unresolved inflammatory disorder, it is perhaps not surprising that telomere erosion in leukocytes is broadly indicative of disease [35].…”
Section: Cause Versus Effect?mentioning
confidence: 99%
“…Also, this gene was in connection with the response to imatinib mesylate treatment in patients with gastrintinal stromal tumors ( Group et al, 2009 ). Recently, rs8105767 variant within ZNF208 gene has attracted much attention in a genome-wide association study related to its relevance to telomere length ( Alves-Paiva et al, 2019 ). This variant was reported to be related to the risk of glioma and soft tissue sarcoma in a genome-wide association study related to its relevance to telomere length ( Vaiciulis et al, 2020 ; Gabriel et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this SNP was not associated with reduced telomere length in squamous cell carcinoma of the head and neck in a Chinese Han population ( Thomas et al, 2007 ). It has been discovered that there is an association between telomere length and head and neck cancer development ( Alves-Paiva et al, 2019 ). The attention has been increasingly focused on investigations of telomeres and telomere length regulating genes, due to their importance in aging and development of chronic diseases and malignant tumors.…”
Section: Introductionmentioning
confidence: 99%